Hemoglobinopathic Erythrocytosis due to a New Electrophoretically Silent Variant, Hemoglobin San Diego (β109(G11)Val→Met) - Nute, Peter E. (1974)
Examination of 13 members of a Filipino family revealed that 6 had erythrocytosis inherited as a simple autosomal dominant trait. Application of several electrophoretic and chromatographic tests failed to reveal the presence of an abnormal hemoglobin in hemolysates from affected individuals. However, measurements of oxygen dissociation curves using whole bloods, dialyzed hemolysates, and 2,3-diphosphoglyceric acid-stripped hemolysates clearly showed that affected persons had an abnormal hemoglobin characterized by a high affinity for oxygen. Compositional analyses of all tryptic peptides from the β-chains of the proband revealed a valyl-methionyl ambiguity in βT12a. Blockage of lysyl residues and subsequent tryptic hydrolysis at arginyl residues permitted the isolation of fragments containing residues 105 through 146. Automatic sequence analysis of the fragments demonstrated the presence of both valine and methionine in nearly equal proportions at position β109. This new hemoglobin variant is designated Hb San Diego (β109(G11) Val→Met).